Preservation of contrasting geothermal gradients across the Caribbean‐North America plate boundary (Motagua Fault, Guatemala). Issue 4 (4th August 2013) - Simon‐Labric, Thibaud; Brocard, Gilles Y.; Teyssier, Christian; van der Beek, Peter A.; Fellin, Maria Giuditta; Reiners, Peter W.; Authemayou, Christine
Abstract : [1] Strike‐slip plate boundaries juxtapose crustal blocks that may have different geodynamic origins and therefore different thermal structures. Thermo‐kinematic modeling of this type of strike‐slip plate boundary predicts an asymmetric signature in the low‐temperature thermochronologic record across the fault. Age‐elevation profiles of zircon (U‐Th)/He ages across the Motagua Fault, a 500 km long segment of the transform boundary between the North American and Caribbean plates, document a sharp cooling age discontinuity across the fault. This discontinuity could be interpreted as a difference in denudation history on each side of the fault. However, a low‐relief Miocene erosional surface extends across the fault; this surface has been uplifted and incised and provides a geomorphic argument against differential denudation across the fault. By integrating magmatic, volcanic, and heat flow data, age‐elevation profiles, and thermo‐kinematic modeling, we propose that large horizontal displacement along the Motagua Fault has offset a persistent geothermal asymmetry across the fault and explains both the age discontinuities and the age‐elevation patterns. This study illustrates how thermochronology can be used to detect large strike‐slip displacements and more generally opens new perspectives in understanding the impact of nonuniform thermal structures on thermochronologic results. Key Points: Effect of geothermal asymmetry on the cooling history of a strike‐slip fault Coupled approach of thermochronology, geomorphology and numerical modeling